Responses of soil bacterial communities and maize yields to sulfur application across four soil types - Dong, Siqi; Zhang, Bing; Wang, Zhao; Zhou, Xue; Gao, Qiang (Frontiers in Microbiology, 2024)
Introduction This study assessed the effects of S application on maize yields and soil bacterial communities across four sites with different soil types and three S application rates (0 kg ha-1, 30 kg ha-1, and 90 kg ha-1). Methods Changes in soil properties, bacterial community diversity, structure, and their contributions to maize production were evaluated post-S application treatments. Results (1) S application decreased soil pH, increased available sulfur (AS), and boosted maize yields in all soil types. (2) Reduced Chao1 and Shannon diversity indices were observed in black soil after S application. (3) Bacterial community structure was significantly affected by S application, except in sandy soil, impacting key stone taxa abundance. (4) Black soil showed higher sensitivity to S application due to less stable bacterial community structure. (5) Soil physicochemical indicators altered by S application, such as AS and pH, mediated bacterial diversity, influencing maize yield. Organic matter (OM) had the most significant direct positive effect on yield, followed by AS and bacterial community diversity. Discussion This study emphasizes the impact of S application on soil properties and bacterial communities in diverse soil types. Understanding these mechanisms can guide precision S application practices for maize yield regulation.